(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the implementation of the Online Single Submission (OSS) at the West Nusa Tenggara Province Investment and One-Stop Integrated Services Agency (DPMPTSP) in supporting ease of doing business. The study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation with informants consisting of two DPMPTSP employees of West Nusa Tenggara Province and two business actors who use the OSS service. Data were analyzed using the Miles and Huberman interactive analysis model which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the OSS is able to increase the efficiency of licensing services through a faster, more practical, and digitally integrated process. The OSS system makes it easier for business actors to manage business legality without having to come directly to the service office, and increases public access to licensing services. However, the implementation of the OSS still faces several obstacles, such as low digital literacy of the community, technical system disruptions, and dynamic regulatory changes. Therefore, increased socialization, mentoring, and strengthening of digital service infrastructure are needed so that the implementation of the OSS can run more optimally in supporting ease of doing business.